1907 Mich. Pub. Acts 68 - (:unkn) unknown (My University, 1907)
An Act Defining the Crime of Burglary with Explosives and Providing the Punishment Therefor, § 1: Any person who with intent to commit crime, breaks and enters any building and for the purpose of committing any crime, uses or attempt to use nitroglycerine, dynamite, gunpowder or any other high explosive shall be deemed guilty of burglary with explosives and on conviction shall be punished by imprisonment for a term of not less than fifteen years nor more than thirty years.
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME